A conceptual paper on examining sponsor response behaviour in esports event: The role of sponsor factor and team identification. - Zailani, Nurul Farah Izzah; Wee, Hassnah; Albattat, Ahmad (International Journal of Accounting, Finance and Business, 2025)
The popularity of esports has grown exponentially in recent years, attracting significant attention from corporate sponsors. However, understanding the factors that influence sponsor response behaviour in the esports context remains a critical research gap. This study aims to examine the role of sponsor factors, team identification in shaping sponsor response behaviour among esports fans. The study aims to understand how sponsor attributes and fan-team identification influence sponsor response during esports events. This approach is particularly relevant given the unique characteristics of the esports environment which includes its digital nature and the varying levels of fan engagement and sponsor awareness. These factors are crucial in shaping audience attitudes and behaviours towards sponsors in this digital and interactive domain. Methodologically, the study employs an exploratory and descriptive research design, utilizing a cross-sectional approach with data collected through online questionnaires. This design is suitable for uncovering new relationships and patterns in the complex esports sponsorship landscape. By exploring these dynamics, the study aims to offer fresh insights into the psychological mechanisms underlying sponsor effectiveness in esports, contributing to both theoretical knowledge and practical applications for sponsors and marketers in this rapidly evolving field. The findings are expected to be valuable for companies sponsoring esports events and organizers seeking to enhance fan engagement and value creation.